Vulvovaginal candidiasis: species distribution of Candida and their antifungal susceptibility pattern - Bitew, Adane; Abebaw, Yeshiwork (BMC women's health, 2018)
Vulvovaginal candidiasis is a global issue of concern due to its association with economic costs, sexually transmitted infections, and ascending genital tract infection. The aim of this study was to determine species distribution and antifungal susceptibility pattern of Candida species causing vulvovaginal candidiasis. A cross sectional study was conducted from November 2015 to December 2016 at the Family Guidance Association of Ethiopia. Vaginal swabs collected from study subjects that were clinically diagnosed with vulvovaginal candidiasis were cultured. Yeast identification and antifungal susceptibility testing were determined by the automated VITEK 2 compact system. The association of vulvovaginal candidiasis with possible risk factors was assessed and analyzed using SPSS version 20. The overall prevalence of vulvovaginal candidiasis was 41.4%. The association of vulvovaginal candidiasis was statistically significant with previous genital tract infection (p = 0.004), number of life-time male sex partners (p = .037), and number of male sex partners in 12 month (p = 0.001). Of 87 Candida isolates recovered, 58.6% were C. albicans while 41.4% were non-albicans Candida species. The highest overall drug resistance rate of Candida species was observed against fluconazole (17.2%), followed by flycytosine (5.7%). All Candida isolates were 100% susceptible to voriconazole, caspofungin, and micafungin. C. albicans, was 100% susceptible to all drugs tested except fluconazole and flycytosine with a resistance rate of 2% each drug. C. krusei, was 100 and 33.3% resistant to fluconazole and flycytosine, respectively. High prevalence rate of vulvovaginal candidiasis and observation of high prevalence rate of non-albicans Candida species in the present study substantiate, the importance of conducting continuous epidemiological surveys to measure changes in species distribution from C. albicans to non-albicans Candida species in Ethiopia. Although, fluconazole still appeared to be active against all isolates of C. albicans and non-albicans Candida species high resistance rate of C. krusei against the drug may demonstrate a search for alternative antifungal drugs when treating vulvovaginal candidiasis caused by C. krusei.